Novel asymmetric 3, 5‐bis(arylidene)piperidin‐4‐one derivatives: synthesis, crystal structures and cytotoxicity. Issue 6 (11th May 2018) - Yao, Binrong; Li, Ning; Wang, Chunhua; Hou, Guige; Meng, Qingguo; Yan, Ke
Abstract : Three asymmetric 3, 5‐bis(arylidene)piperidin‐4‐one derivatives (BAPs) were synthesized and their structures elucidated by single‐crystal X‐ray diffraction. Preliminary evaluations were conducted on their cytotoxicities against HepG2, THP‐1 and LO2. Abstract : 3, 5‐Bis(arylidene)piperidin‐4‐one derivatives (BAPs) display good antitumour activity because of their double α, β‐unsaturated ketone structural characteristics. Reported BAPs have generally been symmetric and asymmetric BAPs have been little documented. Three asymmetric BAPs, namely (5 E )‐3‐(4‐ tert ‐butylbenzylidene)‐5‐(4‐fluorobenzylidene)‐1‐methylpiperidin‐4‐one, C24 H26 FNO, (5 ), (5 E )‐3‐(4‐ tert ‐butylbenzylidene)‐5‐(3, 5‐dimethoxybenzylidene)‐1‐methylpiperidin‐4‐one, C26 H31 NO3, (6 ), and (5 E )‐3‐{3‐[( E )‐(2, 3‐dihydroxybenzylidene)amino]benzylidene}‐5‐(2‐fluorobenzylidene)‐1‐methylpiperidin‐4‐one, C27 H23 FN2 O3, (12 ), were generated by Claisen–Schmidt condensation. They are characterized by NMR and FT–IR spectroscopies, and elemental analysis. Single‐crystal structure analysis reveals that the two arylidene rings on both sides of the BAP structures adopt an E stereochemistry of the olefinic double bonds and the compounds are E, E isomers. Molecules of (5 ) and (12 ) generate one‐dimensional chains through intermolecular hydrogen bonds, while compound (6 ) generates a two‐dimensional network through hydrogen bonds. Preliminary cytotoxicities toward human liver hepatocellular carcinoma cell line (HepG2), human acute mononuclear granulocyte leukaemia (THP‐1) and human normal hepatical cell line (LO2) were evaluated.